Edible fiducial marker made of edible retroreflector. (December 2018) - Oku, Hiromasa; Uji, Takahiro; Zhang, Yiting; Shibahara, Kumi
Highlights: Edible fiducial markers are expected to be important when one try to apply VR/AR technology on foods. This paper reports an edible retroreflector made from transparent foodstuffs, and an edible fiducial marker made from the edible retroreflector. Dynamic projection mapping on foods utilizing these prototypes were demonstrated to show the practical application example. Graphical abstract: Abstract: In Augmented Reality (AR) and Mixed Reality (MR), it is important to measure the position and orientation of objects in the real world. However, there were many difficulties in recognizing objects from images along, especially considering real-time processing. To make the recognition task easier in such cases, markers are commonly utilized. In particular, retroreflectors are often used as markers since they become very bright in captured images and are easy to be detected by image processing. However, most conventional retroreflectors are made from glass or plastic. Thus, it has been difficult to apply them to some fields such as foods or inspection of the inner wall of digestive organs. In this paper, we propose an edible retroreflector made from transparent foodstuff. We found that kanten, or Japanese agar, which is a traditional Japanese cooking ingredient used to form a transparent jelly, was suitable for forming such optical devices. A prototype successfully retroreflected incident light. An edible fiducial marker made of this edible retroreflector material is also proposed. Dynamic projection mapping on food was demonstrated based on two prototypes to show examples of their potential applications.